Interleukin-18 is associated with the presence of interstitial lung disease in rheumatoid arthritis: a cross-sectional study. (4th March 2019) - Matsuo, T; Hashimoto, M; Ito, I; Kubo, T; Uozumi, R; Furu, M; Ito, H; Fujii, T; Tanaka, M; Terao, C; Kono, H; Mori, M; et al.
Abstract : Objective : Serum interleukin-18 (IL-18) levels are increased in patients with interstitial lung disease (ILD). In addition, IL-18 levels are increased in patients with rheumatoid arthritis (RA) and are associated with arthritis activity. We determined whether increased IL-18 levels are associated with ILD in RA. Method : RA patients were enrolled using an RA cohort database. Plasma IL-18 levels were measured by enzyme-linked immunosorbent assay. ILD was determined by a pulmonologist and a radiologist based on chest radiography and computed tomography findings. IL-18 levels for RA with ILD and RA without ILD were compared. Associations between ILD and various markers including IL-18 and confounding factors (e.g. smoking history) were investigated by logistic regression analysis. Diagnostic values of IL-18 for the presence of ILD were investigated using receiver operating characteristics curve analysis. Results : ILD was complicated in 8.2% (n = 26) of the study population (N = 312). Plasma IL-18 levels were higher for RA patients with ILD than for RA patients without ILD (721.0 ± 481.4 vs 436.8 ± 438.9 pg/mL, p < 0.001). IL-18, Krebs von den Lungen-6, and anti-cyclic citrullinated peptide antibody titre and glucocorticoid doses were independently associated with the presence of ILD during multivariate logistic regression analysis. Sensitivity and specificity of IL-18 levels for the detection of ILD in RA patients were 65.3% and 76.3%, respectively (area under the curve = 0.73). Conclusion : Plasma IL-18 levels were higher for RA patients with ILD than for those without ILD. Increased IL-18 levels were associated with the presence of ILD.